2016
DOI: 10.1016/j.carbon.2015.09.095
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent generation at ABA/ABC lateral junction in tri-layer graphene photodetector

Abstract: Metal-graphene-metal photodetectors utilize photocurrent generated near the graphene/metal junctions and have many advantages including high speed and broad-band operation. Here, we report on photocurrent generation at ABA/ABC stacking domain junctions in tri-layer graphene with a responsivity of 0.18 A/W. Unlike usual metal-graphene-metal devices, the photocurrent is generated in the middle of the graphene channel, not confined to the vicinity of the metal electrodes. The magnitude and the direction of the ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…This PTE current has been found to occur at the graphene–metal interface, graphene pn junction, monolayer–bilayer graphene junction, and ABA–ABC stacked graphene domain junction . In these devices, PTE is usually assumed to be dominant over PVE but the contrary has also been reported .…”
Section: Introductionmentioning
confidence: 99%
“…This PTE current has been found to occur at the graphene–metal interface, graphene pn junction, monolayer–bilayer graphene junction, and ABA–ABC stacked graphene domain junction . In these devices, PTE is usually assumed to be dominant over PVE but the contrary has also been reported .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Several studies have revealed the influence of the stacking order on transport 6,7 and optical properties. [8][9][10][11][12] Hence, identifying the stacking sequences has become an important issue, and Raman spectroscopy has proven to be a reliable and easy characterization tool to identify stacking orders in few-layer graphene. [9][10][11]13 Since the Raman spectrum reflects the phonon dispersion and the electronic band structure, it is an ideal tool for fingerprinting the polytypes of graphene without complicated sample preparations.…”
mentioning
confidence: 99%
“…The NEP of the photodetector was measured to be 4 kW/cm 2 , thus an LDR of 44 dB has been obtained in the device which was 4 500 times larger than that of previously reported graphene photodetectors (LDR ≈ 7.5 dB) [154] and ~ 800 times larger than that of other functionalized graphene devices (LDR≈15 dB) [215]. ABA/ABC stacking domain junctions in tri-layer graphene is another FGPD design proposed for photocurrent generation [216]. Figures 20(a) and 20(b) present the stacking structures of 3LG with ABA and ABC stacking sequences [217].…”
Section: Full Graphene Photodetectorsmentioning
confidence: 77%
“…Stacking structures of 3LG[216] with (a) ABA and (b) ABC stacking sequences, (c) schematic of a graphene photodetector with a lateral junction between ABA-and ABC-stacked domains in 3LG (ABA/ABC photodetector), (d) comparison of 2D Raman peak line width (top) and photocurrent (bottom) images of 3 different ABA/ABC photodetectors, and (e) band alignment of the ABA/ABC junction in 3LG for VG = VCNP.…”
mentioning
confidence: 99%